2014
DOI: 10.4194/1303-2712-v14_2_19
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this research, the differences between wild and cultured brown trout (Salmo trutta forma fario Linneaus, 1758) were determined by investigating meat yield, chemical quality and amino acid composition of wild and cultured trout in the East Black Sea region between January and December. The mean meat yield of 67.59%±0.48 in wild trout was significantly higher than that of 64.46%±0.73 in cultured trout (P<0.05). The mean crude protein, crude lipid, moisture contents and crude ash were 17

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
2
6
1
Order By: Relevance
“…When we compared with the previous studies, we thought that the different results may be due to seasonal, biological differences, nutritional, and environmental conditions as well as methods used for amino acid determination. In addition, Kaya et al (2014) found significant differences in monthly amino acid values in their studies (P \ 0.05) like us. Oluwaniyi et al (2010) compared the essential amino acid contents of C. harengus, S. scombrus, T. trachurus, and U. tenuis with the standard amino acid values of FAO/WHO (1991).…”
Section: Decsupporting
confidence: 53%
See 1 more Smart Citation
“…When we compared with the previous studies, we thought that the different results may be due to seasonal, biological differences, nutritional, and environmental conditions as well as methods used for amino acid determination. In addition, Kaya et al (2014) found significant differences in monthly amino acid values in their studies (P \ 0.05) like us. Oluwaniyi et al (2010) compared the essential amino acid contents of C. harengus, S. scombrus, T. trachurus, and U. tenuis with the standard amino acid values of FAO/WHO (1991).…”
Section: Decsupporting
confidence: 53%
“…They stated that the named fish are a good source of nutrients in terms of glutamic acid that required for cell proliferation. Kaya et al (2014) investigated the amino acid content of, Salmo trutta forma fario that hunting and growing on the farms, and they found that glutamic acid, aspartic acid, and lysine values were higher than other amino acids. They found that the differences in total amino acid values were generally significant (P \ 0.05) by species and by age, and they stated that the distinction in amino acid values was due to the spawning season, the feeding conditions, and the living area.…”
Section: Decmentioning
confidence: 99%
“…The content of amino acids in the dry matter of the muscle tissue of the three species of trout (Table 4) revealed that the main amino acids for those fish species were aspartic acid, glutamic acid and lysine. Other authors have reported similar data on those amino acids in trout muscles (Ozyurt and Polat, 2006;Kaya et al, 2014;Sirakov, 2015). However, according to Sarma et al, (2015), the amino acid proline was the main one in the muscles of the rainbow trout.…”
Section: Protein and Amino Acid Profilessupporting
confidence: 63%
“…The established EAA/ NEAA ratio in mackerel mussels is about 0.58 this value was lower than other fish species as cultured and wild brown trout, Scomber japonicus, Sardina melonosticta, and Mugil cephalus which values were about 0.9, 0.96, 0.77, 0.69, 0.71 as reported by Kaya et al, (2014) ;Iwasaki et al, (1985).…”
Section: Amino Acidsmentioning
confidence: 54%
“…All of the cited essential amino acids were found at important quantities in Atlantic mackerel mussels. Moreover, amino acids type and amount in fish mussels are related to catching period, location (Wesselinova, 2000), feeding and spawning season (Kaya et al, 2014). According to Green et al, (2002) essential and non essential amino acids ratio in dietary protein has an important effect on protein utilization by fish.…”
Section: Amino Acidsmentioning
confidence: 99%